Relationship between problem in financial capital, entrepreneurial competencies, social capital, self efficacy and women entrepreneurs' business performance - Yusrinadini Zahirah, Md Isa @ Yusuff (2018)
Currently, the involvement of women in entrepreneurship has become popular subject of academic research. As such, the Malaysian government has set aside a yearly budget for women empowerment as they have vital roles in economic development. Although female entrepreneurship is growing, there are still insufficient studies on the relationship of problem in financial capital, entrepreneurial competencies, social capital, and self-efficacy with the performance of women entrepreneurs. Therefore, this study has focused on the testing of the mediator (social capital) and moderator (self-efficacy) of the aforementioned association in Malaysia. With reference to the literature, four dimensions of entrepreneurial competencies – opportunity, organising and leading, commitment, and personal competencies have been selected. Subsequently, 13 direct and indirect hypotheses have been developed. The respondents were women micro-entrepreneurs under the highest scheme of Amanah Ikhtiar Malaysia (AIM) – Ikhtiar Wawasan – in Peninsular Malaysia. The tools which have been used to measure the said variables were adopted from the scales in the literature. A total of 230 questionnaires have been returned by mail, but only 184 questionnaires were eligible for multiple regression analysis. The findings from an empirical research revealed that problem in financial capital, organising and leading competency, and self-efficacy have significant direct effect on women microentrepreneurs’ business performance. Besides, social capital has fully mediated the relationship between problem in financial capital and women entrepreneurs’ business performance. Conversely, self-efficacy did not moderate the relationship between the dimensions of entrepreneurial competencies and women entrepreneurs’ business performance. The utilisation of general self-efficacy has contributed to the significance of this study. Apart from that, the findings are useful to financial institutions, academics and women micro-entrepreneurs’ in the contexts of financial management of entrepreneurship domain, entrepreneurial management and entrepreneurs’ personality.